As várias faces de um ser mútiplo: construções e apropriações da mulher e autora Florbela espanca (1930-1985) - Farias, Priscilla Freitas de (2023)
The fascination that Florbela Espanca's life and, above all, her suicide exerted on the analyzes of her work, contributed not only to the creation of "myths", but to the very construction of the poet as an author, making her one of the most famous Portuguese poets of the 20th century. Throughout the various critical studies produced about the poet, thousands of “Florbelas” were born and died under different perspectives and representations. In this work, therefore, I do not intend to respond to the problems of Florbelian critical world studies, much less explain the inexplicable — suicide. My objective is to work on the authorial invention of Florbela Espanca. In this way, the analysis of this work intends to go through the speeches of articles in newspapers, magazines, literary reviews and biographies about the author after the suicide. For this, the time frame ranges from 1930 to 1984, that is, from Florbela Espanca's suicide to the discovery of the rest of Florbela Espanca's work and, finally, the publication in Complete Works by businessman Rui Guedes. Thus, based on the theoretical assumption of Michel Foucault (2015), I propose to reflect on the authorial construction of the poet, problematizing the relationship between suicide and the place of women in Portuguese society in the early twentieth century, as well as analyzing the various discourses that shaped the authorial image of Florbela Espanca throughout the 20th century, from the romantic, conservative and moralist discourse to salazarist, regionalist and gender politics.